Persepsi Masyarakat Terhadap Keseimbangan Kerja dan Hidup (Work-Life Balance) Perempuan Karier: Studi di Lingkungan Masyarakat Kota Jambi - Juliana Juliana; Carin Anjani; Delvina Colen Henata; Yossinomita Yossinomita (Prosiding Seminar Nasional Ilmu Teknik, 2025)
This research aims to analyze the public's perception of career women's efforts in achieving work-life balance, as well as its impact on the dual role experience. The research focus includes the view of society, obstacles experienced by women, and the social implications of the dual role of women. The results of the study based on the questionnaire showed that 74,94% of the people had a positive perception of career women and judged that the balance of work and life can be achieved through time management and family support, while 25,06% had a neutral to negative perception that considered that career women were not optimal in carrying out domestic roles, thus causing social pressure and role conflicts. This perception contributes to stress levels, emotional fatigue, and difficulties in achieving work-life balance. This finding also reveals that education factors, working experience with women, family roles, and social environment affect the formation of perceptions. This research is expected to contribute in increasing public understanding and encouraging policies that support women's careers both in social and work.